Annual Plan 2003-2004 Government of Punjab Department of Planning - Planning Commission (Planning Commission, 2003)
Though Punjab encompasses only 1.5% of the geographical area of the country, it produces 21% of wheat, 10% of rice and 8% of cotton of the total produce of these crops in the Country. The State has contributed 51.3% and 51.2% in the central pool of wheat and rice respectively during 2001-2002. But as a result of the adoption of intensive technology to extract the maximum out of the limited resources of land and water, Punjab is now facing problems of degradation of soil health, fast erosion of micro-nutrient reserves, alarming depletion of sweet water table in the central districts and acute menace of alkalinity, salinity and water-logging (in the South Western districts). Consequent upon such intensification, Punjab Agriculture has now reached a plateau beyond which further growth appears to be limited. The major factor behind the serious crisis facing Punjab Agriculture is the traditional wheat-paddy crop rotation which remains dominant despite strenuous efforts to shift area towards water light, ecofriendly/ commercial crops. Today Punjab is also in the tight grip of problem of plenty as certain erstwhile deficit states are fast catching up with Punjab. Therefore, a new orientation to the agriculture sector is immediately required to prepare it to meet the new global challenges.
Annual Plan 2003-2004
Government of Punjab